A REVIEW ON FORMULATION AND CHARACTERIZATION OF NANOEMULSION - AMIN, NURUL; DAS, BISWAJIT (International Journal of Current Pharmaceutical Research, 2019)
Nanoemulsions are clear, thermodynamically stable mixtures of oil, water, surfactant and co-surfactant. These are the oil-in-water type of emulsions with the average droplet size ranging from 5 nm to 100 nm. Nanoemulsions are thermodynamically stable transparent or translucent dispersions of oil and water stabilized by an interfacial film of surfactant and co-surfactant molecules having a droplet size of less than 100 nm. This review provides brief information about the method of preparation and evaluation of nanoemulsion as drug carriers for improving the delivery of therapeutic agents. There are several techniques are to be used for preparation of nanoemulsions like high pressure homogenization, microfluidization, low energy emulsification and solvent evaporation method and parameter that are to be used for its characterization like droplet size analysis, viscosity determination, drug content, refractive index, pH, zeta potential, Transmission electron microscopy, thermal stability, release and in vitro skin permeation study.Nanoemulsion